LASVITA (Android-Based Learning): An Opportunity in Learning Language for High School Grader in Pandemic Situation - Yuanovita Prihatianti Fitria (Musamus Journal of Language and Literature, 2021)
Nowadays, internet is accessible for everyone. The use of internet in Indonesia in 2021 increases significantly compare with with 2019 survey. 202.6 million internet users in Indonesia are detected, and 80% of them are teenagers. Covid-19 pandemic is also one of the reason why mobile access penetration significantly increased. Ironically, the other survey from Statista in 2020 discovered the fact that they use the internet to access social media, especially whatsapp. It may a serious threat for our youngsters. However, this research believe that this is an opportunity to introduce a creative media to catch students’ attention, especially for language teaching and learning. For further, Lasvita, which is an android-based learning application is introduced. This research investigated and analyzed how it can attract the students’ attention, so that they will not depend too much on social media and more productive when they access internet. This research assumes that by having an adequate knowledge, an android-based learning will be no longer become a threat. On the other hand, it will be a vital media to fulfill new need in language learning during during pandemic.